1987
DOI: 10.1128/aem.53.9.2159-2164.1987
|View full text |Cite
|
Sign up to set email alerts
|

Na + -Stimulated Transport of l -Methionine in Brevibacterium linens CNRZ 918

Abstract: The transport of L-methionine by the gram-positive species Brevibacterium linens CNRZ 918 is described. The one transport system (Km = 55 ,uM) found is constitutive for L-methionine, stereospecific, and pH and temperature dependent. Entry of L-methionine into cells is controlled by the internal methionine pool. Competition studies indicate that L-methionine and aL-aminobutyric acid share a common carrier for their transport. Neither methionine derivatives substituted on the amino or carboxyl groups nor D-methi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Cells grown to mid-exponential phase were harvested by centrifugation at 4°C, washed twice with 50 mmol l )1 potassium phosphate, pH 6AE0, and suspended in the same buffer. For transport measurement, cells were energized for 2 min at 30°C with 20 mmol l )1 glucose; then transport was initiated by addition of a labelled amino acid, and at specific time intervals aliquots were removed to measure radioactivity (Ferchichi et al 1987;Gendrot et al 2000). The initial rate of transport was determined from the initial slopes of transport kinetic curves.…”
Section: Methodsmentioning
confidence: 99%
“…Cells grown to mid-exponential phase were harvested by centrifugation at 4°C, washed twice with 50 mmol l )1 potassium phosphate, pH 6AE0, and suspended in the same buffer. For transport measurement, cells were energized for 2 min at 30°C with 20 mmol l )1 glucose; then transport was initiated by addition of a labelled amino acid, and at specific time intervals aliquots were removed to measure radioactivity (Ferchichi et al 1987;Gendrot et al 2000). The initial rate of transport was determined from the initial slopes of transport kinetic curves.…”
Section: Methodsmentioning
confidence: 99%
“…Early work with Escherichia coli indicated that bacterial transport could be coupled to protons (15,16), but subsequent experiments showed that glutamate transport was stimulated by Na (11). It has since become apparent that Na gradients can serve as a driving force for transport in a variety of bacteria (10,18,27,30). The rumen is a Na-rich environment (approximately 90 mM), and recent work indicated that the ruminal bacteria Streptococcus bovis (24) and Peptostreptococcus strain C (7) used Na symport mechanisms to take up neutral amino acids and branched-chain amino acids, respectively.…”
mentioning
confidence: 99%
“…Proton-motive force. When exponentially growing cultures were incubated with [14C]TPP+ and corrected for nonspecific binding (cells treated with 5 or 50 uM valinomycin, 10 uM TCS, or 1% toluene), Aqi was only -3 mV. Very little ['4C]benzoate was taken up, and the intracellular pH (6.67) was lower inside than outside (pH 6.9).…”
mentioning
confidence: 99%